A Survey on the Evolution of Opportunistic Routing with Asynchronous Duty-Cycled MAC in Wireless Sensor Networks - Ayesha Akter Lata; Moonsoo Kang (Sensors, 2020)
Wireless sensor networks (WSNs) have been used for environmental monitoring and reporting for many decades. Energy consumption is a significant research topic because wireless sensor nodes are battery-operated to be highly energy-constrained. Several strategies have been introduced in routing and MAC (Medium Access Control) layer protocols to facilitate energy saving. At the routing layer, an energy-efficient routing protocol, known as opportunistic routing (OR), has been designed to improve efficiency. OR achieves energy efficiency via load-balancing, which forwards packets along multiple routes over WSNs. At the MAC layer, an energy-efficient MAC protocol known as the asynchronous duty-cycled MAC (ADCM) protocol achieves energy saving by turning on and off a sensor node’s transmitter and receiver to eliminate unnecessary energy wastage. These protocols each have their own advantages and disadvantages. OR achieves energy efficiency at the routing layer but it raises an issue at the MAC layer. ADCM achieves energy efficiency at the MAC layer, but it hinders the packet forwarding efficiency of the OR. To attain better energy efficiency, a combination of these two ideas led to the development of OR with asynchronous duty-cycled MAC (OR-ADCM). However, even with better energy efficiency, limitations still exist in combining load-balancing and duty-cycling due to conflicts in the inherent properties of OR and ADCM. In this paper, we present a survey of the evolution of OR-ADCM over WSNs to help the reader better understand and appreciate the details of this tradeoff, which we hope will lead to the development of better protocol designs.